Ibuprofen Release from Poly(ethyl cyanoacrylate) Nanoparticles Prepared by Semicontinuous Heterophase Polymerization. (21st May 2018) - Balleño, J. A.; Mendizábal-Ruiz, A. P.; Saade, H.; Díaz de León-Gómez, R.; Mendizábal, E.; Rios-Donato, N.; López, R. G.
Abstract : Ibuprofen-loaded poly(ethyl cyanoacrylate) nanoparticles were prepared by semicontinuous heterophase polymerization of ethyl cyanoacrylate in the presence of ibuprofen; different surfactant concentration, pH, and temperature were used. Particle size was measured by quasi-light scattering and transmission electron microscopy, while the amount of drug released was determined by UV spectroscopy. Nanoparticles with diameters between 10 and 58 nm, loaded with ibuprofen, were obtained. The smallest particles and the higher drug loading were obtained at the highest pH tested. The analysis of the release data showed that the drug release profiles correspond to the Weibull model. Moreover, it was found that most of the ibuprofen is released within the first 80–120 min; initially the release rate is slow, but then it increases to finally decrease. This behavior contrasts with the reported burst of drug concentration in the plasma after oral administration of IB.